Reduced Mortality of Staphylococcus aureus Bacteremia in a Retrospective Cohort Study of 2139 Patients: 2007–2015 - Austin, Eloise D (Clin Infect Dis, 2020)
BACKGROUND: Understanding the changing epidemiology of Staphylococcus aureus bacteremia, as well as the variables associated with poor outcomes, can yield insight into potential interventions. METHODS: This study was a retrospective, observational cohort study of adult patients at an academic medical center in New York City who had S. aureus bloodstream infections between 1 January 2007 and 31 December 2015. Participants were divided into 3 periods: group 1 (2007–2009), group 2 (2010–2012), and group 3 (2013–2015) for trend analysis. All clinical strains were genotyped (spa.). The main outcome was 30-day all-cause mortality. RESULTS: There were 1264 episodes of methicillin-susceptible S. aureus (MSSA) and 875 episodes of methicillin-resistant S. aureus (MRSA) bacteremia, with a rising proportion due to MSSA (55% group 1; 59% group 2; 63% group 3; P = .03.) There were no significant changes in average age, gender, Charlson score, and distribution of strain genotypes. Mortality in MRSA infection was unchanged (25% group 1; 25% group 2; 26% group 3), while mortality in MSSA infection significantly declined (18% group 1; 18% group 2; 13% group 3). The average time to antistaphylococcal therapy (AST) in MSSA infection declined during the study (3.7 days group 1; 3.5 group 2; 2.2 group 3). In multivariate analysis, AST within 7 days of initial positive MSSA culture was associated with survival. CONCLUSIONS: Mortality in MSSA bloodstream infection is declining, associated with a decrease in time to targeted therapy. These results emphasize the potential for rapid diagnostics and early optimization of treatment to impact outcomes in MSSA bacteremia.